SNe Ia from double detonations: impact of core-shell mixing on the carbon ignition mechanism - Gronow, Sabrina; Collins, Christine; Ohlmann, Sebastian T.; Pakmor, Rüdiger; Kromer, Markus; Seitenzahl, Ivo R.; Sim, Stuart; Röpke, Friedrich (Astronomy and astrophysics, 2020)
Sub-Chandrasekhar mass white dwarfs accreting a helium shell on a carbon-oxygen core are potential progenitors of normal Type Ia supernovae. This work focuses on the details of the onset of the carbon detonation in the double detonation sub-Chandrasekhar model. In order to simulate the influence of core-shell mixing on the carbon ignition mechanism, the helium shell and its detonation are followed with an increased resolution compared to the rest of the star treating the propagation of the detonation wave more accurately. This significantly improves the predictions of the nucleosynthetic yields from the helium burning. The simulations were carried out with the AREPO code. A carbon-oxygen core with a helium shell was set up in one dimension and mapped to three dimensions. We ensured the stability of the white dwarf with a relaxation step before the hydrodynamic detonation simulation started. Synthetic observables were calculated with the radiative transfer code ARTIS. An ignition mechanism of the carbon detonation was observed, which received little attention before. In this “scissors mechanism”, the impact the helium detonation wave has on unburnt material when converging opposite to its ignition spot is strong enough to ignite a carbon detonation. This is possible in a carbon enriched transition region between the core and shell. The detonation mechanism is found to be sensitive to details of the core-shell transition and our models illustrate the need to consider core-shell mixing taking place during the accretion process. Even though the detonation ignition mechanism differs form the converging shock mechanism, the differences in the synthetic observables are not significant. Though they do not fit observations better than previous simulations, they illustrate the need for multi-dimensional simulations.